La inclusión digital y el diseño curricular de Lengua: Un abordaje didáctico-disciplinar de la brecha digital - González López Ledesma, Alejo Ezequiel; Alvarez, Guadalupe; Bassa, Lorena (Universidad de Costa Rica, 2019)
In this article we present the results of a research aimed at understanding the way in which digital media have been integrated in the curricular design of the Language discipline for the basic level of Argentina´s secondary schools. This study is framed within a broader line of inquiry that seeks to give depth to reflections on the ways in which the curriculum of this discipline has been challenged by the digital inclusion processes carried forward in high school and analyse the pedagogical reach of digital inclusion politics. To carry out this exploratory analysis, we have used a qualitative research approach and, particularly, the content analysis method, which is organized into three sequential phases: the preanalysis, the examination of the content and the interpretation of the results. Among the results, we have found three guidelines for the integration of digital media: Internet as a source of information for the teaching of oral argumentation; the electronic support as a source of information for the teaching of reading and the word processor as an editing tool for the teaching of reading and writing. In conclusion, we note that the integration of digital media is compatible with the disciplinary movement of reconfiguration which has taken place in recent years and we reflect on the didactic positions that we understand are necessary to face change and innovation in the school.